Enhancing concurrent transactions processing mechanisms - Nariman Adel Hussein Naser; Hoda Mokhtar Omar Mokhtar (Cairo : Nariman Adel Hussein Naser, 2014)
Software transactional memory (STM) is an alternative to the traditional lock-based approach to express and manage concurrency. An effective way to reduce the number of aborts in STM is to keep multiple versions of the objects. We propose efficient object-based implementations for STM. The proposed implementations are based on using multiple versions of the objects to overcome the problem of rejecting operations that arrive late to be serialized. In this work, we propose 3 algorithms for enhancing concurrency in STM. We also propose a new approach for deleting the useless versions
Thesis (M.Sc.) - Cairo University - Faculty of Computers and Information - Department of Information System
Issued also as CD
Keywords: Concurrency Control Mechanisms; Concurrent Transactions; Contention Management